Book Review Motivasi dan Kepribadian: Perspektif Islam tentang Dinamika Jiwa dan Perilaku Manusia - Tri Astuti; Bagus Riyono (Faculty of Cultural Sciences, Universitas Gadjah Mada, 2023)
The book discussed in this article is titled Motivasi dan Kepribadian: Perspektif Islam tentang Dinamika Jiwa dan Perilaku Manusia. This book was written by Dr. Bagus Riyono, M.A., a psychologist and lecturer in the Faculty of Psychology at Universitas Gadjah Mada and is currently president of the International Association of Muslim Psychologists (IAMP). This book is 284 pages long and consists of several chapters, all of which deconstructing pre-existing theories of motivation, as well as constructing pioneering theories of motivation using various research approaches, including qualitative approach using “meta-ethnographically-grounded-theory” and quantitative approach using experimental method (Riyono, 2020. p. 89). All this was done so that the researcher could achieve comprehensive research results.